Bottleneck and Rework Analysis of the Budget Approval at University with Process Mining - Syakurnia, Barajati; Bryan Ronald Talisman; Sahra Bilqis Fauziyyah; Faturrahman; Rachmadita Andreswari (Faculty of Computer Science (FILKOM) Brawijaya University, 2023)
Process mining is a new science that focuses on the transparency of an existing process. Especially in a world full of digitalization, of course, many companies, education, health are immediately competing in presenting the most efficient and effective processes to do. in this study the authors used Request for Payment data owned by a university. These requests will later be checked by the travel administration, this budget approval can be done by supervisors, directors, or fund owners. the author uses Celonis tools and algorithms in Celonis to identify bottlenecks and rework in the process. We also attempted to analyze where new insights could be drawn from the resulting process model. The result of this research is to pay special attention to several activities, as well as to provide explanations of the criteria related to the application to be submitted.